PECULIARITIES OF SPORADIC VARIATIONS IN DENSITY AND ANISOTROPY OF GALACTIC COSMIC RAYS IN SOLAR CYCLE 24 - V.G. Grigoryev; S.K. Gerasimova; P.Yu. Gololobov; S.A. Starodubtsev; A.S. Zverev (Solar-Terrestrial Physics, 2022)
In this work, we have processed data from the global network of neutron monitors and muon telescopes by the global survey method to study variations in the density and anisotropy of galactic cosmic rays during Forbush decreases observed in solar cycle 24. The simultaneous use of two different type detectors made it possible to examine the temporal dynamics of the angular distribution of cosmic rays in two different energy intervals. Besides, we have used measurements of the Yakutsk cosmic ray spectrograph after A.I. Kuzmin to assess the energy spectrum index during large disturbances of the interplanetary medium in this cycle. Analysis of the results obtained confirms our early statements that solar activity cycle 24 features an increased level of turbulence in the interplanetary magnetic field.